A periphery lost: the representation of Karelia in Finnish national landscape imagery - Häyrynen, Maunu (Geographical Society of Finland, 2004)
The article reflects how Karelia has been represented as a national periphery in Finnish national landscape imagery, understood as a dynamic system of social representations defining Finland as national space. Karelia may be likened to other national peripheries, analysed among others by Robert Shields as liminal zones allegedly at the margins of society. The particular aspects of Karelian landscape occurring in popular landscape imagery are discussed. It is pointed out how these anchor Karelia to a variety of contexts, of which Karelianist imagery originating from art constitutes only one. Similarly the ideological roles of Karelian landscape have varied, starting from the didactic narratives of Zachris Topelius and ending up in the post-war and post-Soviet Karelian revivals. However, the present-day Karelian landscape is a nostalgic construction, transferring the liminal zone outside history.